Karl Polanyi: the limits of the market - Dale, Gareth (Key contemporary thinkers series, 2010)
Karl Polanyi: The Limits of the Market is the first comprehensive introduction to Polanyi's ideas and legacy. It assesses not only the texts for which he is famous – prepared during his spells in American academia – but also his journalistic articles written in his first exile in Vienna, and lectures and pamphlets from his second exile, in Britain. It provides a detailed critical analysis of The Great Transformation, but also surveys Polanyi’s seminal writings in economic anthropology, the economic history of ancientand archaic societies, and political and economic theory. Its primary source base includes interviews with Polanyi's daughter, Kari Polanyi-Levitt, as well as the entire compass of his own published and unpublished writings in English and German. This engaging and accessible introduction to Polanyi's thinkingwill appeal to students and scholars across the social sciences,providing a refreshing perspective on the roots of our currenteconomic crisis.
Keywords: economics; philosophy

Polanyian meditations on economy and society: a review of 'Market society: the great transformation today' - Dale, Gareth (Dialectical anthropology, 2010)
Keywords: book review; cultural ethnography; economic anthropology; market economy; society